Chemical modification of brown macro algae Padina sp. as a potential biosorbent for the removal of heavy metals in aqueous solution / Anies Suhaida Mohd Naspu - Mohd Naspu, Anies Suhaida (2016)
Chemical modification on brown macro algae Padina sp. as biosorbent was carried out in order to enhance the performance due to the inefficient in removing metal ion from the water bodies. Brown macro algae Padina sp. was undergoing NaCl pretreatment process before applying it with citric acid and PAA/HC1. After modifications, characterization of biosorbent was observed using FTIR and SEMEDX analysis. FTIR analysis shows that the modified Padina sp. was enhanced the intensity and functional groups presence on the biosorbent. However, Padina-PAA shows the greatest reduction in it intensity due to the binding of metal ions on active sites compared to Padina-CA and pre-treated Padina. The surface morphology of Padina sp. slightly change after pre-treatment but there are no significant changes observed between Padina-C A and Padina-PAA. The presence of metal ions on biosorbent after adsorption process was confirmed using SEM-EDX. Batch of experiments were conducted to determine the optimum removal of metal ions by considering few parameters such as contact time, pH, initial metal ions concentration and biosorbent dosage. It found that 75 minutes is the best exposure time for pretreated Padina and Padina-C A and 60 minutes for Padina-PAA. pH of 6 , 100 ppb of initial concentration and 0.5 g of biosorbent dosage resulting the optimum removal metal ion by all the biosorbents. Meanwhile, Pb ion is dominant in removal followed by Cd, Cu, Ni and Cr. Adsorption-desorption study was performed using HNO3 as desorbing agent and the result shows that the regeneration of biosorbent is up to 5 cycles with 80% recovery. Equilibrium isotherm model was good fit to the Freundlich isotherm model which describes the heterogeneity metal binding and pseudo-second order is the best kinetic model to describe the biosorption on the rate limiting step. Among o f three biosorbent tested, chemical modification of Padina sp. with PAA/HC1 shows the best performance in removing metal ions from water system.